Pain Improvement Among Chronic Lumbar Disc Herniation Patients Underwent Epidural Triamcinolone With Or Without Hyaluronidase Injection Within 3 Months Of Follow-Up: A Prospective Study - Budisulistyo, Trianggoro; Husni, Amin; Tugasworo, Dodik; Pudjonarko, Dwi (RSUP Dr. Kariadi, 2023)
Background Chronic lumbar disc herniation (CLDH) will accompany by chronic inflammation, so the fibrosis tissues formed in the epidural space and adjacent nerve roots, and lead to mixed pain syndrome. Objectives To compare between triamcinolone only and hyaluronidase 1500 international unit (IU) administration epidural injection for treating bulged or protrusion CLDH. Methods This prospective study involved CLDH patients visiting the outpatient department of Neurology at Dr. Kariadi Hospital Semarang Indonesia from November 2021 until August 2022. They divided: triamcinolone (Group 1) and hyaluronidase 1500 IU and triamcinolone epidural injection (Group 2) with 3 days of hospitalization. Neurotrophic was prescribed during 3 months of follow-up and ordered for personal physical treatment. They analyzed pain improvements (NRS and Pain DETECT), and the Oswestry Disability Index (ODI) scores. Results The 37 subjects were recruited but 1 female dropped out cause of re-injection, so 13 males and 23 females aged between 24 to 72 years old (mean 48+2) were followed. They significantly improved (Wilcoxon test p=.000), as the NRS score was 47.9% (Group 1) and 55.4% (Group 2). ODI scores without significance (Mann-Whitney p> .005), such at 2 weeks (group 1= 20.4%, group 2= 23.6%) and 3 months (group 1= 58.1%, group 2= 53.7%). They observed nociceptive and neuropathic improvement even though needed more time for the healing process. Conclussions This study proved hyaluronidase administration before triamcinolone epidural injection with better improvements for treating bulged or protrusion CLDH patients.